Pengembangan Sistem Pemantauan Perkuliahan Jurusan Teknik Informatika Universitas Halu Oleo Berbasis Website dengan Agile Development Methods - Rayadin, Muhamad Amhar; Billa, Nabilla Salsa; Thalib, La Ode Jafar Umar; Saputra, Rizal Adi (Program Studi Teknik Informatika Universitas Pamulang, 2024)
To keep up with the ongoing progress in information and communication technology, the administration of academic activities at the Department of Informatics Engineering at Halu Oleo University must adjust its methods to ensure optimal efficiency and precision. An important aspect is the monitoring of lectures, which now depends on a manual approach, such as traditional methods of documenting attendance. Common problems include extended data processing time, vulnerability to data loss, and frequent recording errors. To tackle these difficulties, this work utilizes the Agile Extreme Programming approach to construct a web-based lecture monitoring system. The system is designed to streamline the process of recording and tracking professor attendance by engaging all pertinent stakeholders, such as class coordinators, lecturers, and administrators. The system offers versatility to students and professors in data management, while also allowing administrators to oversee course information, faculty members, students, and academic terms. The adoption of the Agile Extreme Programming methodology in the development of this web-based lecture monitoring system has effectively addressed the efficiency issues encountered in the lecture monitoring process at the Department of Informatics Engineering, Halu Oleo University. Adopting a web-based system has enhanced the efficiency of academic activity management by replacing manual signature-based attendance sheets. This transition has facilitated the recording of lecturer attendance and the monitoring of lectures. The research findings underwent evaluation through the black box testing methodology and produced outcomes consistent with anticipated outcomes.